PENGEMBANGAN MODEM AFSK UNTUK TELEMETRI MUATAN ROKET UHF - Wahyu Widada (National Institute of Aeronautics and Space - LAPAN, 2006)
Modem is an important component in the telemetry data system of the rocket. The telemetry data based on amateur radio is usually used an AFSK modem. This paper describes the development of AFSK modem using a microcontroller which the speed can be set to the maximum bandwidth of the radio. The prototype is use a 16 MHz of microcontoller and the speed can be set to 2.4 kbps that available to the standard bandwidth of an amateur radio. Keywords: AFSK modem, Band-rate, Telemetry, Roket, Telemetry, UHF.